REWRITING CIVILIZATION BASED ON SCIENTIFIC REVOLUTION: CURRENT RESEARCH FINDINGS FROM ARCHAEOLOGICAL SITES IN INDONESIA - Akbar, Ali (International Review of Humanities Studies, 2023)
The research on civilization in Indonesia has been conducted since 1800s. Around 1970s, there was theory regarding Out of Africa stating that ancient human was from Africa then spread to all over places in the world. Besides, around 1980s there was opinion theory regarding Out of Taiwan which stated that modern human culture spread from Taiwan to South East Asia. Different research findings then are considered anomaly and barely accepted as science. Revolution could occur when the new different evidences from previous science are found. The findings of archaeology from last ten years in Indonesia have some potential to trigger scientific revolution.